Analisis transformasi ruang hunian program rumah subsidi pemerintah - Agustina Sri Rezeki Simbolon; Dwira Nirfalini Aulia; Hilma Tamiami Fachrudin (ARTEKS : Jurnal Teknik Arsitektur, 2021)
The government is currently conducting programs to provide subsidized housing in order to meet the needs of low-income people. Some of the houses provided have, however, been modified by the residents to ensure proper and effective implementation of their activities and this indicates a benchmark of the dissatisfaction of the residents and omission of a particular thing in the initial design of the subsidized housing program provided by the government. The Grand Permata Residence II Housing used as a case study has a house with type 36/91 m2 and 13 out of 14 respondents have transformed their residential space according to their economic capacity as low-income people. This study was, therefore, conducted to map the residential space transformation of the subsidized housing program provided by the government and determine the causative factors. Primary data were obtained in the form of designs and photos of space transformation through direct observation and interviews with residents while secondary data were in the form of initial floor plans retrieved from the housing manager and analyzed using descriptive analysis techniques. The findings serve as an evaluation for the government in designing subsidized housing which meets the target and needs of low-income people.